LITERATUR REVIEW: FITOTERAPI UNTUK AROMATERAPI DAN PENYAKIT DEPRESI - Nawwar Irfan; Syafitri; Nur Atika; Juliana Dara; Auliya Rabbani (PT. Hasba Edukasi Mandiri, 2026)
Depression is one of the most common psychological disorders and can significantly affect an individual’s quality of life. In addition to conventional pharmacological therapy, aromatherapy using plant-derived essential oils has been widely applied as a complementary treatment to reduce depressive symptoms. This study aimed to review the potential of aromatherapy-based phytotherapy in the management of depression through a literature review. Articles were collected from Google Scholar and PubMed using the keywords aromatherapy, depression, and essential oils. A total of 20 relevant articles were selected based on inclusion and exclusion criteria, and 10 main journals were analyzed. The results indicate that several essential oils, including bergamot, gardenia, jasmine, lavender, ylang-ylang, peppermint, cinnamon, lemon, pandan, as well as Plumeria alba and Michelia alba, exhibit antidepressant, anxiolytic, anti-stress, and relaxing effects. Overall, aromatherapy using essential oils has potential as a safe and easily applicable complementary therapy to help reduce depressive symptoms. Further studies with stronger experimental designs are required to support its clinical application.